2011
DOI: 10.5601/jelem.2011.16.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnesium on pork quality

Abstract: Over the recent years, there has been an increasing interest in improving pork quality, which at present often fails consumer requirements. Nutritional regime is one of the key environmental factors affecting fattening results, slaughter value and meat quality. The technological and organoleptic properties of pork can be modified through feeding. Numerous studies have been conducted to determine the effect of diet composition on meat quality.Consumers prefer lean pork with a bright reddish-pink color, and they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
(32 reference statements)
2
8
0
Order By: Relevance
“…The presence of magnesium in opoka at a significant level is probably the reason for the increased WHC factor determined in leg muscles of male and female broilers fed with opoka-supplemented diet (Table 4). According to literature data, magnesium-supplemented diet improved water-binding capacity of pig meat (58)(59)(60), similarly as in our results. According to Houston and Harper [61], magnesium regulates pH and intracellular levels of Ca, Na, K. Close relationship and mutual interaction between Mg and K ions due to the level of their concentration in muscles is also well known [62,63].…”
Section: Whc (Water Holding Capacity)supporting
confidence: 92%
“…The presence of magnesium in opoka at a significant level is probably the reason for the increased WHC factor determined in leg muscles of male and female broilers fed with opoka-supplemented diet (Table 4). According to literature data, magnesium-supplemented diet improved water-binding capacity of pig meat (58)(59)(60), similarly as in our results. According to Houston and Harper [61], magnesium regulates pH and intracellular levels of Ca, Na, K. Close relationship and mutual interaction between Mg and K ions due to the level of their concentration in muscles is also well known [62,63].…”
Section: Whc (Water Holding Capacity)supporting
confidence: 92%
“…However, the reduced ultimate pH may have contributed to significantly higher scores for ‘salty taste’ that were observed in high-FE meat. This is in agreement with Lipinski et al [ 33 ] who previously found that meat with lower pH can be perceived by sensory panellists as more salty.…”
Section: Discussionsupporting
confidence: 93%
“…Solubility, reactivity, and bioavailability are all characteristics that differ from one MgO product to another [ 4 ]. The mineral feed bioavailability is also different: for example, the average Mg bioavailability of magnesium oxide, compared to magnesium phosphate, is around 20 vs. 45% [ 15 ].…”
Section: Mg In Farm Animals’ Dietmentioning
confidence: 99%